Deviation And poetical Language Of AmalDingl - Graykous, Tayseer; sulaiman, Fadia (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The displacement method of the important methods in stylistic studies and modern linguistics; it is based onDepart from the familiar and ordinary language to create beauty creative outlines a literary text by the poet and increase its luster, and its showText aesthetic statement and the possibility of the poet and his abilities shift in his words, which the recipient is a matter of contemplation and interpretation Revealed in a metaphorical sense, it stands on aesthetic and poetic language. And here it highlights the role of the imagination in the production of diverse literary images, since the poet called free rein to his imagination in the generation of meanings andInnovation, and this is done in the familiar skip weave method, and breach of the modest traditions between language users, If the purpose of the distortion of the text is to create beauty and stylistic innovation that leaves an impact on its recipients, which confirms Position Poetic language; Art is not art until breathing shed from the standard, and even filled his intention of violating the order and violation of norms, That's what the beauty of D poets, literary texts semantic my style.